Development of a laboratory-based learning model via digital platform environment - Dao, Van-Phuong; Nguyen, Thi-Luong; Bui, Van-Hong; Tran, Vu-Hoang; Phan, Phuong Nguyen-Truc; Nguyen, Minh-Dao (Frontiers in Education, 2025)
The online teaching and learning method can implement synchronous and asynchronous processes for theory courses using digital platforms through digital education systems. Implementing online teaching and learning for laboratory courses presents challenges, as synchronous is infeasible due to the requirement for specialized tools, equipment, and experimental materials. An asynchronous teaching and learning model can be used instead. In this study, we proposed an Asynchronous online teaching and learning model tailored for practice laboratory-based courses in engineering and technology education. This model is named “Development of a Laboratory-Based Learning Model via a Digital Platform Environment.” This model is proposed based on the student-feedback interaction model, and called the online feedback practice model. The proposed model is experimented with teaching and learning laboratory-based subjects. The experiment involved two groups of 200 students, including 100 students in the control group (face-to-face practice) and 100 students in the experimental group (online feedback practice). Both groups participated in a final evaluation through direct in-class assessments. The research results demonstrated that the model yields higher effectiveness than the traditional method, based on evaluating statistical analysis to compare average scores, outcomes, achievement rate, and assignment completion rate of two student groups. The model also gathered feedback from instructors teaching in the same field regarding the course's learning outcomes, which have been validated to meet AUN-QA standards. The survey results are also statistically evaluated and calculated through means, variances, standard deviations, and hypotheses using t-tests to demonstrate the effectiveness of the proposed model.